Methodological and Reporting Quality of Noninferiority Randomized Controlled Trials Comparing Antibiotic Therapies: A Systematic Review. (9th September 2020) - Bai, Anthony D; Komorowski, Adam S; Lo, Carson K L; Tandon, Pranav; Li, Xena X; Mokashi, Vaibhav; Cvetkovic, Anna; Kay, Vanessa R; Findlater, Aidan; Liang, Laurel; Loeb, Mark; Mertz, Dominik
Abstract: Background: Antibiotic noninferiority randomized controlled trials (RCTs) are used for approval of new antibiotics and making changes to antibiotic prescribing in clinical practice. We conducted a systematic review to assess the methodological and reporting quality of antibiotic noninferiority RCTs. Methods: We searched MEDLINE, Embase, the Cochrane Database of Systematic Reviews, and the Food and Drug Administration drug database from inception until November 22, 2019, for noninferiority RCTs comparing different systemic antibiotic therapies. Comparisons between antibiotic types, doses, administration routes, or durations were included. Methodological and reporting quality indicators were based on the Consolidated Standards of Reporting Trials reporting guidelines. Two independent reviewers extracted the data. Results: The systematic review included 227 studies. Of these, 135 (59.5%) studies were supported by pharmaceutical industry. Only 83 (36.6%) studies provided a justification for the noninferiority margin. Reporting of both intention-to-treat (ITT) and per-protocol (PP) analyses were done in 165 (72.7%) studies. The conclusion was misleading in 34 (15.0%) studies. The studies funded by pharmaceutical industry were less likely to be stopped early because of logistical reasons (3.0% vs 19.1%; odds ratio [OR] = 0.13; 95% confidence interval [CI], .04–.37) and to show inconclusive results (11.1% vs 42.9%; OR = 0.17; 95% CI, .08–.33). The quality of studies decreased over time with respect to blinding, early stopping, reporting of ITT with PP analysis, and having misleading conclusions. Conclusions: There is room for improvement in the methodology and reporting of antibiotic noninferiority trials. Quality can be improved across the entire spectrum from investigators, funding agencies, as well as during the peer-review process. There is room for improvement in the methodology and reporting of antibiotic noninferiority trials including justification of noninferiority margin, reporting of intention-to-treat analysis with per-protocol analysis, and having conclusions that are concordant with study results. Clinical Trials Registration PROSPERO registration number CRD42020165040. Abstract : There is room for improvement in the methodology and reporting of antibiotic non-inferiority trials including justification of non-inferiority margin, reporting of intention-to-treat analysis with per-protocol analysis, and having conclusions that are concordant with study results.